Bionomics of Aedes aegypti subpopulations (Diptera: Culicidae) from Argentina - Grech, Marta Gladys (2010)
Differences in biological features of immature and adult Aedes aegypti, as well as variability in vector competence, seem consistent with the existence of genetic variation among subpopulations and adaptation to local conditions. This work aims to compare the bionomics of four Ae. aegypti subpopulations derived from different geographical regions reared under temperate conditions. Life statistics of three Ae. aegypti subpopulations from the provinces of Córdoba, Salta, and Misiones were studied based on horizontal life tables. The Rockefeller strain was used as a control. The development time required to complete the larva and pupa stages varied from 6.91 to 7.95 and 1.87 to 2.41 days, respectively. Significant differences were found in mean larval development time between the Córdoba and Orán subpopulations. The larva-pupa development time was similar in all the subpopulations. However, survival values varied significantly between the Orán and San Javier subpopulations. The proportion of emergent males did not differ from females within each subpopulation nor among them. Adult longevity was similar among the subpopulations. The average number of eggs laid by each female was significantly different. The Rockefeller strain laid a significantly greater number of eggs (463.99 eggs/female) than the rest of the subpopulations. Moreover, differences in the demographic growth parameter Ro were detected among the four subpopulations. The differences obtained in larval development time, larva-pupa survival values, and net reproductive rates among the subpopulations might reflect underlying genetic differences as a result of colonization from different regions that probably involve adaptations to local conditions.